Carbon nanotubes and xerogels as supports of well dispersed Pt catalysts for environmental applications - Gomes, Helder (2009)
Different types of carbon materials including multi-walled nanotubes (MWNT), carbon xerogels (CX) and activated carbon (AC) were used as supports to prepare platinum catalysts (1% w/w), which were tested in the treatment of aqueous aniline solutions by catalytic wet air oxidation (CWAO). The prepared materials and catalysts were characterized by several techniques (SEM/EDS, TEM, N2 adsorption, TPD and H2 chemisorption). All catalysts presented a very high activity for the removal of aniline and total organic carbon (TOC). Catalyst activity and selectivity toward CO2 formation were found to depend on the nature of the support and concentration of oxygen containing functional groups on the surface of the materials.